2010
DOI: 10.1039/c003040f
|View full text |Cite
|
Sign up to set email alerts
|

Donor–acceptor polymers based on multi-fused heptacyclic structures: synthesis, characterization and photovoltaic applications

Abstract: We report here two novel 2,7-fluorene- and 2,7-carbazole-based conjugated polymers PFDCTBT and PCDCTBT containing ladder-type heptacyclic structures with forced planarity. PCDTBT shows excellent solubility, low band gap and high hole mobility, leading to a power conversion efficiency of 3.7%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 30 publications
1
77
0
Order By: Relevance
“…The device using P80:PC 71 Alternating copolymers poly(2,7-fluorene-alt-dithienylbenzothiadiazole) (PFD TBT) [119] and poly(2,7-carbazole-alt-dithienylbenzothiadiazole) (PCDTBT) [120] have been a promising class of p-type photoactive materials for the application in PSCs. Cheng et al [121] reported two D-A copolymers poly(fluorene-dicyclopentathiophenealt-benzothiadiazole) P81 and poly(carbazole-dicyclopentathiophene-alt-benzothiadiazole) P82. Both polymers were designed based on the skeletons of the well-known PFDTBT and PCDTBT polymers.…”
Section: Conjugated Polymers Containing Multifused Alternatementioning
confidence: 99%
“…The device using P80:PC 71 Alternating copolymers poly(2,7-fluorene-alt-dithienylbenzothiadiazole) (PFD TBT) [119] and poly(2,7-carbazole-alt-dithienylbenzothiadiazole) (PCDTBT) [120] have been a promising class of p-type photoactive materials for the application in PSCs. Cheng et al [121] reported two D-A copolymers poly(fluorene-dicyclopentathiophenealt-benzothiadiazole) P81 and poly(carbazole-dicyclopentathiophene-alt-benzothiadiazole) P82. Both polymers were designed based on the skeletons of the well-known PFDTBT and PCDTBT polymers.…”
Section: Conjugated Polymers Containing Multifused Alternatementioning
confidence: 99%
“…Taking this into account, Hsu et al reported two new ladder-typed polymers P9 and P10, which were prepared by copolymerization of the heptacyclic donor (fluorenedicyclopentathiophene or carbazole-dicyclopentathiophene) with the BT acceptor. Through such a simple and straightforward engineering of molecular side chains, the large π-conjugated coplanar P9 and P10 simultaneously possess excellent solubility for solution processability, low band gaps with suitable position of HOMO/ LUMO energy levels, and high hole mobilities, leading to promising PCEs of 3.7 [19] In 2011, Hsu's group reported a nonacylic thienyl-phenylene-thienylenephenylene-thienyl (TPTPT) donor unit that consists of alternate thiophene and benzene units fused by four embedded cyclopentadienyl rings. Copolymer P12 with TPTPT as the donor unit and BT as the acceptor unit was synthesized by Stille cross-coupling reaction and used as donor material for the fabrication of PSCs.…”
Section: Bt-based Donor Polymers For Photovoltaic Applicationmentioning
confidence: 99%
“…Cheng et al . reported another larger coplanar carbazole -related unit which contained seven fused rings and could be copolymerized with benzothiadiazole to yield d5 , which gave a PCE of 3.7% when blended with PC 71 BM [47] .…”
Section: Polycarbazole Derivativesmentioning
confidence: 99%